Unbundled : A Framework for Connecting Safety Nets and Humanitarian Assistance in Refugee Settings - Seyfert, Karin; Barca, Valentina; Gentilini, Ugo; Luthria, Manjula; Abbady, Shereen (World Bank, Washington, DC, 2019)
The debate on if and how to connect humanitarian assistance for refugees with national social protection systems can elicit polarizing views. Hence, it is not unusual to observe country-level approaches getting somewhat ‘stuck’ – especially where refugees represent a sizable share of the population: from a donor perspective, the question is how can governments be persuaded to be more inclusive; from a government standpoint, it faces disproportionate political and economic risks from “being left with the bill”; and from the international humanitarian agencies viewpoint, there might be quandaries on how to reconcile commitments to neutrality and independence with those to respecting the primary responsibility of governments. These stylized views are legitimate, but their combined effect may generate competing narratives and little negotiating space among the multiple actors involved. The net result might be the endurance of a sub-optimal dual systems operating in parallel – one for refugees, one for citizens. The framework laid out in this paper attempts to facilitate the identification of workable pathways for progress among actors. Instead of framing the humanitarian-social protection links as an ‘either-or’ choice, the framework includes a more granular analysis of how collaborations may emerge around select programmatic ‘functions’, as well as the ‘degrees’ of possible connection between national and international support within a given function.